2020
DOI: 10.1113/jp279230
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment improves the exaggerated exercise pressor reflex in rats with femoral artery occlusion via a reduction in the activity of the P2X receptor pathway

Abstract: Key pointsr During exercise, the blood pressure (BP) response is exaggerated in peripheral artery disease (PAD).r We examined whether heat treatment (HT) has beneficial effects on the exaggerated exercise pressor reflex in PAD rats.r With HT (increase in basal muscle temperature of ß1.5°C for 30 min, twice daily for three continuous days), the amplified BP response to muscle contraction is alleviated in PAD.r We demonstrated that HT attenuates the enhancement of the BP response induced by stimulation of P2X in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 53 publications
(96 reference statements)
2
14
1
Order By: Relevance
“…With the approach of ventral root stimulation in the current study, it was observed that the BP response to the skeletal muscle contraction was enhanced in PAD rats when compared with the control rats. This result was also consistent with what observed in the previous studies ( Liu et al, 2011 ; Qin et al, 2020 ). In addition, the exaggerated BP response was attenuated following increasing Tm by ~1.5°C ( Figure 2A ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…With the approach of ventral root stimulation in the current study, it was observed that the BP response to the skeletal muscle contraction was enhanced in PAD rats when compared with the control rats. This result was also consistent with what observed in the previous studies ( Liu et al, 2011 ; Qin et al, 2020 ). In addition, the exaggerated BP response was attenuated following increasing Tm by ~1.5°C ( Figure 2A ).…”
Section: Discussionsupporting
confidence: 94%
“…The elevated ATP concentration in the muscle interstitium enhances the expression and function of P2X 3 and the subsequent EPR response is exaggerated. Consistent with previous studies (Liu et al, 2011;Qin et al, 2020), the BP response following both muscle contraction and muscle stretch was higher in rats with femoral artery occlusion than that in control rats (Figures 2A,B). BP response to stimulation of P2X 3 by injection of αβ-me ATP, as a part of EPR activation, was also amplified in PAD rats (Figures 3A,B).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations